Practices Regarding the Forms of Communication with the Consumers used by a Multinational Company at Global and Local Level - Madalina Dumitru; Nadia Albu; Valentin Florentin Dumitru; Catalin Nicolae Albu (Amfiteatru Economic Journal, 2014)
This study is motivated by the importance of communication with consumers in the pharmaceutical industry. We view communication as part of the company's responsibility towards consumers. The aim of this study is to examine the communication mechanisms of corporate social responsibility practices related to consumers in the pharmaceutical industry in a multinational, by comparing the Romanian's subsidiary practices with the global ones. The data is extracted from the annual reports issued by a multinational company from 2010 to 2012 and from the only social responsibility report issued by its Romanian subsidiary (2011). The information is analysed both form a quantitative and a qualitative point of view. We employ the legitimacy theory, and particularly the three types of legitimacy – pragmatic, moral, and cognitive, in order to analyse the reporting practices. We find differences in the reporting channels and forms between the global firm and the Romanian subsidiary. Also, the results are important for the specialized literature and indicate that the multinational uses different types of legitimizing discourse than its subsidiary. We contribute to a better understanding of the corporate social responsibility reporting by addressing the communication towards the consumer as a key stakeholder and by investigating the manner in which reporting works at global and local levels.
Keywords: M14; Q56; 330; communication; consumers; organizations' responsibility; pharmaceutical industry; legitimacy theory